Primary Elements Impacted by the Risk of Disappearance and Deterioration of the Betawi Language in the Community - Iskandarsyah Siregar; Arju Susanto (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
The Betawi language, akin to many global languages, is on the brink of fading due to various factors, one being the evolution of civilization. This decline jeopardizes several facets of the native Betawi culture. Hence, efforts to maintain and preserve the Betawi language are imperative. The challenge lies in understanding the extensive scope of Betawi's linguistic and textual context. Thus, it's crucial to develop a targeted strategy that pinpoints the primary elements influenced by the degradation and endangerment of the language, particularly in the Betawi community. This study identifies these elements after extensive on-field research, spanning over a year with round-the-clock observations. The research found that a sociological qualitative analysis, especially focusing on society's social evaluation, is the most effective method. Consequently, five key areas were identified to analyze the repercussions of the language's decline: linguistic aspects, individual identity, inter-generational communication, knowledge transfer, and economic implications